Rethinking the translator (in)visibility in the field of web news: some proposals for the academic education in translation - Garcia Simao, Angelica Karim [UNESP]; Andrade Stupiello, Erika Nogueira de [UNESP] (Univ Sao Paulo, Fac Filosofia, 2017)
Technological advances in the late 20th century resulted in transformations not only in news writing, but also in the role played by translators working in these emerging contexts. This scenario has defined a new set of challenges for translators working in direct and immediate dialogue with extratextual constraints (cultural, historical and ideological aspects) that have always been part of the translation profession. Such challenges require a better-delineated professional profile to qualify translators to develop specific translation strategies for the journalistic context. In this paper we reflect on the reconfiguration of the role of translators working with journalistic texts in the 21st century, as well as on the way this role can be understood within an academic translation education program aimed at developing skills and competencies that can qualify translators to work in this market segment.
Keywords: translation; journalism; strategies